Idiosyncratic risk and spillover effect in REIT returns - Hui, Eddie C. M.; Wang, Ziyou (International Journal of Strategic Property Management, 2018)
Nowadays, idiosyncratic risk has substantial impacts on the risk control of portfolio construction. However, little research has been done on the spillover effect of idiosyncratic risk from global markets in REIT returns. A risk-return model is developed to examine the effects of idiosyncratic risk and its spillover on the short-run dynamics of REIT returns in 10 major REIT markets between 2001 and 2014. Variance decomposition provides evidence that idiosyncratic risk exceeds market risk most of the time. The risk-return models demonstrate that the spillover effect of idiosyncratic risk globally played a more significant role than idiosyncratic risk in the return dynamics during the subprime mortgage crisis. Furthermore, we analyse the asymmetric responses of volatility in REIT returns. The results show that the Netherlands is the most strongly preferred market in terms of earning excess returns, while the US market is unique in that the idiosyncratic risk and spillover effect tend to enlarge the fluctuations in REIT returns.